2023
DOI: 10.1021/jacs.3c02511
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Aberrarone

Abstract: The structurally intriguing diterpene (+)-aberrarone has been assembled in only 12 steps from the commercially available (S,S)-carveol without protecting group manipulations. This concise synthesis features a Cu-catalyzed asymmetric hydroboration to generate the chiral methyl group, a Ni-catalyzed reductive coupling to link two fragments, and a Mn-mediated radical cascade cyclization to construct the triquinane system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…To date, the total syntheses of aberrarone (92) have been described by Carreira 49 and Jia. 50 In 2022, Carreira et al reported the first total synthesis of (+)-aberrarone (92) in 15 steps using a creative Au-catalyzed Nazarov cascade reaction. 49 In 2023, Jia et al disclosed a 12step protocol to (+)-aberrarone (92) via a radical cascade reaction 50 which will be discussed herein (Scheme 10).…”
Section: Metal-catalyzed Reductive Cross Coupling Reaction In Total S...mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the total syntheses of aberrarone (92) have been described by Carreira 49 and Jia. 50 In 2022, Carreira et al reported the first total synthesis of (+)-aberrarone (92) in 15 steps using a creative Au-catalyzed Nazarov cascade reaction. 49 In 2023, Jia et al disclosed a 12step protocol to (+)-aberrarone (92) via a radical cascade reaction 50 which will be discussed herein (Scheme 10).…”
Section: Metal-catalyzed Reductive Cross Coupling Reaction In Total S...mentioning
confidence: 99%
“…50 In 2022, Carreira et al reported the first total synthesis of (+)-aberrarone (92) in 15 steps using a creative Au-catalyzed Nazarov cascade reaction. 49 In 2023, Jia et al disclosed a 12step protocol to (+)-aberrarone (92) via a radical cascade reaction 50 which will be discussed herein (Scheme 10). Their synthesis began with the preparation of alkyl iodide (93) and vinyl iodide (94).…”
Section: Metal-catalyzed Reductive Cross Coupling Reaction In Total S...mentioning
confidence: 99%
See 1 more Smart Citation
“…A few months later, the group of Jia reported a different synthesis of the same natural product . Jia’s approach involved intermediates 101 and 102 , synthesized in 2 steps from commercial compounds.…”
Section: Identifying the Right Key Step(s) For Concise Synthesesmentioning
confidence: 99%
“…Among these creative solutions, two-electron transformations play a dominate role in the construction of the central ring system and the polycyclic structures. Here we report our work on the concise and divergent synthesis of scabrolide A ( 1 ) and havellockate ( 2 ) through a rare exo - exo - endo radical cascade, which is notably different from all previous works.…”
mentioning
confidence: 99%